An analysis of affixation in Sasak language dialect - Fahimah Saifuddin; Lalu Dwi Satria Adriansyah (Journal of Research on English and Language Learning (J-REaLL), 2022)
This study aims to show how many affixations in Sasak Language Meriak-Meriku dialect and the semantic meaning. The methodology used in this study is qualitative method by following two steps. Those are: Firstly, the researcher reads the English book that consists of affixes both inflection and derivation. Seconddly, the researcher writes all the data collected. This study based on David H. Deterding, Gloria R. Poedjosoedarmo, William O’Grady, and Michael Dobrovolsky theories about affixation both inflection and derivation. Finally,the result of this study is in Sasak language dialect Mriak-Mriku has nine affixations that have different meaning.